2019
DOI: 10.15193/zntj/2019/120/303
|View full text |Cite
|
Sign up to set email alerts
|

Wpływ serwatki kwasowej na jakość fizykochemiczną i stabilność barwy fermentowanych kiełbas ekologicznych

Abstract: Celem pracy była ocena wpływu serwatki kwasowej na wybrane właściwości fizykochemiczne i stabilność barwy fermentowanej kiełbasy wieprzowej po procesie dojrzewaniu oraz po 7 i 14 dniach chłodniczego przechowywania (4 ºC). Materiał doświadczalny stanowiła kiełbasa wieprzowa surowo dojrzewająca z dodatkiem serwatki kwasowej i soli morskiej. Przygotowano dwa warianty kiełbas: próbę kontrolną poddaną peklowaniu oraz próbę z dodatkiem serwatki kwasowej i soli morskiej. Oceny dokonywano bezpośrednio po procesie dojr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(37 reference statements)
3
0
0
Order By: Relevance
“…Compounds formed during the proteolytic decomposition of proteins demonstrated a buffering effect against organic acids produced by lactic acid bacteria during the fermentation process and refrigerated storage. This is supported by the findings of other authors [25,26,[28][29][30]. In addition, the pH values observed in this study throughout the production period may enhance the high antioxidant potential of the product.…”
Section: Assessment Of Physicochemical Parameters During Ripeningsupporting
confidence: 91%
See 2 more Smart Citations
“…Compounds formed during the proteolytic decomposition of proteins demonstrated a buffering effect against organic acids produced by lactic acid bacteria during the fermentation process and refrigerated storage. This is supported by the findings of other authors [25,26,[28][29][30]. In addition, the pH values observed in this study throughout the production period may enhance the high antioxidant potential of the product.…”
Section: Assessment Of Physicochemical Parameters During Ripeningsupporting
confidence: 91%
“…According to these authors, the storage time of raw-ripened products significantly affects oxidative changes in the product, with the observed increase in TBARS attributed to the accumulation of fat decomposition products. The significant (p < 0.05) decrease in TBARS index values recorded in this study for all analyzed samples between 51 and 81 days of ripening was also observed by Lorenzo et al [28], Ge et al [48], and Oko ń et al [29]. Samples with dandelion addition had the lowest TBARS values, supporting the hypothesis of its antioxidant properties.…”
Section: Assessment Of Antiradical Potential Of Raw-ripening Pork Sau...supporting
confidence: 88%
See 1 more Smart Citation